A lead-based room-temperature phosphorescent metal–organic framework sensor for assessing the peroxide value of edible oils. (15th August 2022) - Wu, Zisen; Wei, Jie; Jiao, Tianhui; Chen, Qingmin; Oyama, Munetaka; Chen, Quansheng; Chen, Xiaomei
Highlights: A RTP sensor was first developed to monitor PV using Pb-MOF as a luminescent probe. The coordination of Pb(II) to TPA induce phosphorescence. The sensor displays simple, rapid and sensitive properties for PV. A test strip was prepared for the detection of PV. The RTP sensor was utilized to monitor the PV in real samples. Abstract: The peroxide value (PV) is an important indicator to assess quality of edible oils. However, traditional methods for determining PV are complicated for operating and lack sensitivity. In this paper, we report a fast, reusable, selective and sensitive room-temperature phosphorescence (RTP)-based sensor to determine the PV of edible oils. The sensor comprises a lead-based metal–organic framework (Pb-MOF, Pb4 O(TPA)3, TPA: (terephthalic acid). Luminescence studies reveal that bright RTP of Pb-MOF quenched significantly by iodide ions (I − ), a classic reductant for peroxides in edible oils, thus the determination of the PV is possible. Crucially, the proposed method yields responses within 10 min and has a wide linear range of 0.35–25.62 mmol/kg, a low detection limit of 30 μmol/kg, and high selectivity for PV detection. The sensing system was successfully applied to determine the PVs of edible oils and monitor the PV of rapeseed oil during storage.